Going Green Circle "Greenferris" Written Report Technology Venture Blueprint / Nur Adawiyah Batrisyia Mustafa - Mustafa, Nur Adawiyah Batrisyia (2020)
The company mission is aimed to emerge a platform that the SME entrepreneurs can improve their ability to boost the socio-economic standing, as well as that of their families and neighbourhoods. Other than that, the company aims to improve the design and the quality of the innovative product at an affordable price. Our company also is inspired to construct the product with high technologies to fulfil the customers’ demand.